2004
DOI: 10.1300/j064v24n03_09
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Input Use Efficiency in Tobacco Production with Respect to Sustainability: The Case Study of Turkey

Abstract: The purpose of this paper is to analyze the efficiency of input use in tobacco production in Turkey with respect to sustainability. In the construction of cross sectional data, the provinces in the Aegean, Northwestern, Eastern-Southeastern Anatolian and Black Sea regions were considered. Face to face interviews were carried out with 300 farmers from the provinces which together produce at least 75% of regional tobacco output. Efficiency measures of tobacco farms in each region were calculated by Data Envelopm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…However, these are separate concepts which should not be replaced. In an enterprise with efficient production levels, an increase in the productivity would not be expected, while an enterprise with increased productivity levels may not be an efficient one (Abay et al 2004). An important point to consider when measuring productivity and efficiency is the definition of productivity used by the manager or the researcher, and the selection of the outputs and inputs used as the indicators of productivity (Donthu et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…However, these are separate concepts which should not be replaced. In an enterprise with efficient production levels, an increase in the productivity would not be expected, while an enterprise with increased productivity levels may not be an efficient one (Abay et al 2004). An important point to consider when measuring productivity and efficiency is the definition of productivity used by the manager or the researcher, and the selection of the outputs and inputs used as the indicators of productivity (Donthu et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…They showed that DEA is more robust than the parametric approach in measuring the productive efficiencies. Abay et al (2004) studied the efficiency of energy consumption in tobacco production in Chauhan et al (2006) used the DEA method to study the efficiency of rice farms in terms of energy consumption. They showed that 11.6% of input energy could be saved in these farms.…”
Section: Efficiency Analysis In Agriculturementioning
confidence: 99%
“…In another work, Abay et al (2004) analysed DEA CCR efficiency measurements of input use in tobacco production in Turkey with respect to sustainability. The authors carried out face-to-face interviews with some 300 farmers.…”
Section: Dea Models and Agricultural Sustainabilitymentioning
confidence: 99%
“…Some authors have proposed the use of DEA models to measure agricultural sustainability as, for instance, Kim (2001), De Koeijer et al (2002, Abay et al (2004), Rodríguez-Díaz et al (2004), Bosetti and Locatelli (2006), Sauer and Abdallah (2007). These studies are briefly described in Sect.…”
Section: Introductionmentioning
confidence: 99%